Resilient cultural practices for cognitive development during childhood within learning pathways with support from mediated mutual reciprocal theory - Tchombe, Therese Mungah Shalo (Frontiers in Psychology, 2023)
Introduction This paper examines resilient cultural practices, informed by cultural values for cognitive development in socialisation during childhood within the learning pathways model. It argues that the active role of children in their learning is not well captured or explained by theories or even empirical data. Learning pathways as a model in this paper is significant because it orients thinking on the fact that all activities children engage in always have social, psychological, and physical implications for cognitive enrichment. The activities are driven by resilient cultural practices informed by cultural norms, beliefs, and values such as responsible leadership qualities and cultivating socio-emotional and moral balance. With the above reasoning, this paper is underpinned by an empirical study with six specific objectives supported by Mediated Mutual Reciprocity theory. Methods The study used a mixed research design and conveniently selected a sample of 73 parents and teachers whose ages ranged from 25-50 years. A questionnaire and an interview guide were used for data collection. The three-sections questionnaire was constructed to find out information about resilient cultural practices and cognitive development. The items in sections two and three were rated on a 5 points Likert scale based on the occurrence of practices and behaviours. The interview guide was constructed to find out information on the three learning pathways; physical, social and psychological that are relevant to children in African cultures. Data were analysed using frequency and proportions and Multiple Regression Analysis to aggregate scores for given conceptual components. Analysis of qualitative data followed the systematic process of thematic and content analysis. Results Based on qualitative findings, it was realised that African children are exposed to physical, social, and psychological pathways to learning. Quantitative results showed that 85.5% of respondents are high in their resilient cultural practices whereas 14.5% of them are low in resilient cultural practices. In the same line, 74.4% of respondents’ cognitive development is high while a proportion of 25.6% is low. The inferential statistics showed that resilient cultural practices are significantly predictive of cognitive processes, reasoning, skills, and strategies at a 0.000 level of significance. Discussion Based on the use of the principles of the Mediated Mutual Reciprocal Theory, the study affirms the importance of children’s contributory role in their learning and cognitive development. The link between pathways, resilient cultural practices, and cognitive development highlights the significance of children’s involvement in their development through participation.